Integrating and utilizing cyber threat intelligence in security operation centers - Vainio, Laura (2025)
This research focuses on the integration and utilization of cyber threat intelli-gence in security operation centers. As cyber threat intelligence continues to grow in significance for organizations to aid in defending against emerging threats, proper practical application models especially for security operation centers remain underdeveloped or non-existent. This master's thesis intends to answer the gap between the need for effective CTI implementation in SOCs and the lack of guiding models. The research methodology used in this thesis is design science research. The produced artifact is a process model for a secu-rity operation center to integrate and utilize cyber threat intelligence in their daily operational services. The developed process model combines the cyber threat intelligence life cycle loop with customization of its outputs for various security operation center services, easing the service delivery with the aid of CTI.